Formação de NH₃, H₂S e HCI durante a co-gasificação de carvão com C.D.R. - Dias, Mário (2006)
In order to deepen the knowledge about coal and R.D.F. co-gasification in fluidized bed gasifiers in terms of gas quality and to understand the behaviour of nitrogen, sulphur and chlorine in a reducing atmosphere this dissertation is presented. The effect of operational parameters such as fuel composition, temperature, E (Equivalence Ratio) and oxygen/steam ratio, which are, according to several authors, the most important parameters that have impact on gas quality and on the behaviour of sulphur, nitrogen and chlorine, was studied. The best results were obtained for blends with little amounts of coal or, even, with no coal at all (R100C0, R70C30), for a temperature range between 800-850ºC, an ER between 0,0-0,2 and for steam flow rates higher then the oxygen flow rates. Another important conclusion is that the amounts of municipal solid wastes generated in Portugal, could and should be used in energetic valorisation processes that contemplate gasification, with the possibility of producing a gas of medium heating value with low concentration of NH₃, H₂S e HCI, by manipulating the operational parameters. The use of a gas with these characteristics in burning systems for energy production would be advantageous energetically and environmentally, since it would lead to a reduction of sulphur and nitogen oxides as well as the reduction of acid gases' emissions.